2021
DOI: 10.1016/j.healthplace.2021.102626
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequalities in distance to and participation in a community-based running and walking activity: A longitudinal ecological study of parkrun 2010 to 2019

Abstract: Objectives To conduct a longitudinal ecological analysis of the distance to and participation in free weekly outdoor physical activity events ( parkrun ) in England from 2010 to 2019, and related socioeconomic and ethnic inequalities, to inform policies to support participation in physically active community events. Methods We calculate distance to the nearest parkrun event for each English Lower Layer Super Output A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
1
6
1
Order By: Relevance
“…Individuals who had no exposure to the various PA awareness campaigns were also among the more vulnerable groups (rank 9). These results are consistent with previous studies, that PA participation is determined by access to PA facilities and health-related information [ 3 , 17 ]. Further, half of sample (52.8%) had never been exposed to any PA awareness campaigns.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Individuals who had no exposure to the various PA awareness campaigns were also among the more vulnerable groups (rank 9). These results are consistent with previous studies, that PA participation is determined by access to PA facilities and health-related information [ 3 , 17 ]. Further, half of sample (52.8%) had never been exposed to any PA awareness campaigns.…”
Section: Discussionsupporting
confidence: 93%
“…Urban-rural and regional disparities in PA have been documented worldwide. With regard to exposure to health promotion initiatives and access to PA amenities, urban dwellers and those who reside in the more developed regions of the world accumulated more PA minutes than their rural counterparts [1,6,[16][17][18]. However, this study found PA inequality in all regions of Thailand, with the largest gaps in Bangkok.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…This includes recurrent ‘parkruns’ in local parks on Saturday mornings across the globe. Studies in the UK and South Africa show parkrun's inclusive, non‐competitive nature and how running with others creates casual sociability and a local sense of place (de Vries et al., 2022; Hindley, 2020; Smith et al., 2021). This focus on sociability resonates with Larsen and Bærenholdt (2019) and Vink and Varró's (2021) studies of smaller running events in Denmark and the Netherlands.…”
Section: Eventsmentioning
confidence: 99%
“…Participation in parkrun is free: people register online and receive a unique 'barcode' containing their parkrun ID number that they take to any event across the world that is scanned and used to log attendance and completion time. An increasing proportion of events have been established in more socioeconomically disadvantaged areas in the UK, with higher population density resulting in better geographical access to events for those living in these areas [12,13]. Inequalities in registration and participation persist despite parkruns being located closer to more socioeconomically disadvantaged areas [12,14] with 13.1% of those participating at least once live in the most socioeconomically deprived areas of the UK (see Table 1).…”
Section: Introductionmentioning
confidence: 99%